2007
DOI: 10.2116/analsci.23.1097
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Determination in Marine Sediment Using Ultrasound for Sample Preparation

Abstract: This work deals with As determination in marine sediment using ultrasound for sample preparation. It is shown that As can be quantitatively extracted from marine sediment using 20% (v/v) HCl and sonication. The slurry is centrifuged and the analyte is determined in the supernatant by hydride generation atomic absorption spectrometry (HG AAS). A flow injection (FI) system is employed for hydride generation, with 0.5% (m/v) NaBH4 used as reducdant and a 20% (v/v) HCl used as sample carrier. The limit of quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…If the As is on the surface of the particles, then total dissolution should not be necessary and relatively mild extractants can be used. Bentlin et al 162 dissolved As in marine sediment by sonication in 20% (v/v) HCl followed by HG-AAS determination. For a sample mass of 0.200 g in 50 mL and an injection volume of 800 mL, the LOQ was 2 mg g À1 .…”
Section: Chemical Vapour Generationmentioning
confidence: 99%
“…If the As is on the surface of the particles, then total dissolution should not be necessary and relatively mild extractants can be used. Bentlin et al 162 dissolved As in marine sediment by sonication in 20% (v/v) HCl followed by HG-AAS determination. For a sample mass of 0.200 g in 50 mL and an injection volume of 800 mL, the LOQ was 2 mg g À1 .…”
Section: Chemical Vapour Generationmentioning
confidence: 99%
“…3,4 Bentlin et al proposed an extraction procedure using an ultrasound probe for the quantitative extraction of inorganic arsenic species in marine sediment samples. The experimental conditions optimized proposed a sample mass from 50 to 500 mg, 20% (v/v) hydrochloric acid solution, and a sonication time of 30 s using a probe with a power of 80 W. 5 Garcia-Casillas et al evaluated the use of an ultrasound probe as an alternative to the conventional standard procedures of metal ion extraction in soils using the following solutions: 0.01 M calcium chloride, 0.43 M acetic acid and 0.05 ethylenediaminetetraacetic acid at pH 7.0. The results demonstrated that the extraction time using calcium chloride solution was reduced from 3 h (conventional procedure) to 2 min using the probe.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic determination plays an important role in the analysis of environmental samples [1][2][3][4][5][6][7][8][9][10]. Metabolism studies of arsenic are widely performed [11][12][13][14][15][16] as well as toxicity studies of arsenic species [17][18][19].…”
Section: Introductionmentioning
confidence: 99%